Underlying Factors of Attitude and Intention towards Knowledge Sharing among Hospitality Employees in Indonesia - Indarti, Nurul; Rachel Luturmas, Join (Journal of Indonesian Economy and Business (JIEB), 2016)
Studies on knowledge sharing attitudes and intention in the context of hospitality industries such as hotel has still a relatively little attention. This current study was intended to fulfill that void to contribute to the existing discussion on knowledge sharing studies for hotel businesses. The main objective of the current study was to examine 1) the effect of extrinsic motivation, absorptive capacity, channel richness, sense of self-worth on attitude towards knowledge sharing, and 2) the effect of attitude towards knowledge sharing on intention of knowledge sharing. The study mainly used theory reasoned action as a point of departure to understand the attitude and intention of knowledge sharing and proposed six hypotheses. We conducted survey among 300 employees from various hotels in Eastern Part of Indonesia (the city of Ambon) and the data was tested using Structural Equation Modelling (SEM) techniques. The findings showed that the extrinsic motivation, absorptive capacity, and in-role behaviour have a positive effect on the attitude of sharing knowledge. In addition, the attitude of knowledge sharing has a positive influence on the intention to share knowledge. Meanwhile, the effect of channel richness and the sense of self-worth on attitude of knowledge sharing were not supported.